2023
DOI: 10.1136/bmjopen-2022-065729
|View full text |Cite
|
Sign up to set email alerts
|

Model-based estimation of burden of COVID-19 with disability-adjusted life years and value of statistical life in West Bengal, India

Abstract: ObjectivesThe COVID-19 pandemic has posed unprecedented challenges to health systems and populations, particularly in India. Comprehensive, population-level studies of the burden of disease could inform planning, preparedness and policy, but are lacking in India. In West Bengal, India, we conducted a detailed analysis of the burden caused by COVID-19 from its onset to 7 January 2022.SettingOpen-access, population-level and administrative data sets for West Bengal were used.Primary and secondary outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…According to a survey from Australia in 2015, it was reported that the three diseases with the largest DALYs were pneumococcal pneumonia, influenza, and herpes zoster, especially in the elderly over 65 years [ 23 ]. It seems that each country or region has different types of disease burden, which are influenced by its national budget for healthcare financing, different resources, and infrastructures between low-income and middle- or high-income countries, as shown by the results of global studies [ 27 , 28 , 29 ] as well as local studies in India [ 30 ] and China [ 31 ]. As mentioned above, the impact caused by COVID-19 during the pandemic cannot be overlooked [ 30 , 32 , 33 , 34 ].…”
Section: Infection Threat In the Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…According to a survey from Australia in 2015, it was reported that the three diseases with the largest DALYs were pneumococcal pneumonia, influenza, and herpes zoster, especially in the elderly over 65 years [ 23 ]. It seems that each country or region has different types of disease burden, which are influenced by its national budget for healthcare financing, different resources, and infrastructures between low-income and middle- or high-income countries, as shown by the results of global studies [ 27 , 28 , 29 ] as well as local studies in India [ 30 ] and China [ 31 ]. As mentioned above, the impact caused by COVID-19 during the pandemic cannot be overlooked [ 30 , 32 , 33 , 34 ].…”
Section: Infection Threat In the Elderlymentioning
confidence: 99%
“…It seems that each country or region has different types of disease burden, which are influenced by its national budget for healthcare financing, different resources, and infrastructures between low-income and middle-or high-income countries, as shown by the results of global studies [27][28][29] as well as local studies in India [30] and China [31]. As mentioned above, the impact caused by COVID-19 during the pandemic cannot be overlooked [30,[32][33][34].…”
Section: Infection Threat In the Elderlymentioning
confidence: 99%